PERBEDAAN PERSEPSI TERHADAP TERPAAN ARTIKEL MAJALAH - Rannie Rachaju (Prodi Ilmu Komunikasi FISIP Universitas Langlangbuana, 2017)
Gender is not the only thing that determines the perception of the individual, although sometimes it has a significant effect. But there are many other things that affect a person's perception, such as one's attention to the object to be perceived or whether there is a social unity of the respondent, and ultimately result in a behavior that is almost uniform when buffeted by certain incentives. This also happens because every individual is active in finding information and getting additional cognition from various sources that he believes about problems related to the exposure. And supported by the media that can meet their respective needs for information.